Biochemical markers after the Norseman Extreme Triathlon - Nyborg, Christoffer (PLoS One, 2020)
Prolonged exercise is known to cause changes in common biomarkers. Occasionally, competition athletes need medical assistance and hospitalisation during prolonged exercise events. To aid clinicians treating patients and medical teams in such events we have studied common biomarkers after at The Norseman Xtreme Triathlon (Norseman), an Ironman distance triathlon with an accumulated climb of 5200 m, and an Olympic triathlon for comparison. Blood samples were collected before, immediately after, and the day following the Norseman Xtreme Triatlon (n = 98) and Oslo Olympic Triathlon (n = 15). Increased levels of clinical significance were seen at the finish line of the Norseman in white blood cells count (WBC) (14.2 [13.5–14.9] 109/L, p < 0.001), creatinine kinase (CK) (2450 [1620–3950] U/L, p < 0.001) and NT-proBNP (576 [331–856] ng/L, p < 0.001). The following day there were clinically significant changes in CRP (39 [27–56] mg/L, p < 0.001) and Aspartate Aminotransferase (AST) (142 [99–191] U/L, p < 0.001). In comparison, after the Olympic triathlon distance, there were statistically significant, but less clinically important, changes in WBC (7.8 [6.7–9.6] 109/L, p < 0.001), CK (303 [182–393] U/L, p < 0.001) and NT-proBNP (77 [49–88] ng/L, p < 0.01) immediately after the race, and in CRP (2 [1–3] mg/L, p < 0.001) and AST (31 [26–41] U/L, p < 0.01) the following day. Subclinical changes were also observed in Hemoglobin, Thrombocytes, K+, Ca2+, Mg2+, Creatinine, Alanine Aminotransferase and Thyroxine after the Norseman. In conclusion, there were significant changes in biomarkers used in a clinical setting after the Norseman. Of largest clinical importance were clinically significant increased WBC, CRP, AST, CK and NT-proBNP after the Norseman. This is important to be aware of when athletes engaging in prolonged exercise events receive medical assistance or are hospitalised.